Discriminating normal regions within cancerous hen ovarian tissue using multivariate hyperspectral image analysis. (29th January 2019) - Akbari Lakeh, Mahsa; Tu, Anqi; Muddiman, David C.; Abdollahi, Hamid
Abstract : Rationale: Identification of subregions under different pathological conditions on cancerous tissue is of great significance for understanding cancer progression and metastasis. Infrared matrix‐assisted laser desorption electrospray ionization mass spectrometry (IR‐MALDESI‐MS) can be potentially used for diagnostic purposes since it can monitor spatial distribution and abundance of metabolites and lipids in biological tissues. However, the large size and high dimensionality of hyperspectral data make analysis and interpretation challenging. To overcome these barriers, multivariate methods were applied to IR‐MALDESI data for the first time, aiming at efficiently resolving mass spectral images, from which these results were then used to identify normal regions within cancerous tissue. Methods: Molecular profiles of healthy and cancerous hen ovary tissues were generated by IR‐MALDESI‐MS. Principal component analysis (PCA) combined with color‐coding built a single tissue image which summarizes the high‐dimensional data features. Pixels with similar color indicated similar composition. PCA results from healthy tissue were further used to test each pixel in cancerous tissue to determine if it is healthy. Multivariate curve resolution‐alternating least squares (MCR‐ALS) was used to obtain major spatial features existing in ovary tissues, and group molecules with the same distribution patterns simultaneously. Results: PCA as the predominating dimensionality reduction approach captured over 90% spectral variances by the first three PCs. The PCA images show the cancerous tissue is more chemically heterogeneous than healthy tissue, where at least four regions with different m/z profiles can be differentiated. PCA modeling assigns top regions of cancerous tissue as healthy‐like. MCR‐ALS extracted three and four major compounds from healthy and cancerous tissue, respectively. Evaluating similarities of resolved spectra uncovered the chemical components that were distinct in some regions on cancerous tissue, serving as a supplementary way to differentiate healthy and cancerous regions. Conclusions: Two unsupervised chemometric methods including PCA and MCR‐ALS were applied for resolving and visualizing IR‐MALDESI‐MS data acquired from hen ovary tissues, improving the interpretation of mass spectrometry imaging results. Then possible normal regions were differentiated from cancerous tissue sections. No prior knowledge is required using either chemometric method, so our approach is readily suitable for unstained tissue samples, which allows one to reveal the molecular events happening during disease progression.